Criteria for the appropriate treatment of osteoporotic vertebral compression fractures - Anselmetti, Giovanni Carlo; Bernard, Jason; Blattert, Thomas; Court, Charles; Fagan, Dan; Fransen, Hendrik; Fransen, Patrick; Sabharwal, Tarun; Schils, Frederic; Schupfner, Rupert; Siddiqi, Mashood; Stoevelaar, Herman; et al. (Pain physician, 2013)
The heterogeneity of patients with osteoporotic vertebral compression fractures (VCF) necessitates a tailored approach of balancing the benefits and limitations of available treatments. Current guidelines are divergent, sometimes contradictory, and often insufficiently detailed to guide practice decisions. - This study aimed at establishing treatment recommendations at the patient-specific level. - Using the RAND/UCLA Appropriateness Method (RAM), the appropriateness of different treatment options for osteoporotic VCFs was assessed. - The assessment was conducted by a European multidisciplinary panel of 12 experts. - The appropriateness of non-surgical management (NSM), vertebroplasty (VP), and balloon kyphoplasty (BKP) was determined for 128 hypothetical patient profiles. These were unique combinations of clinical factors considered relevant to treatment choice (time since fracture, MRI findings, impact and evolution of symptoms, spinal deformity, ongoing fracture process, and pulmonary dysfunction). After 2 individual rating rounds and plenary meetings, appropriateness statements (appropriate, inappropriate, and uncertain) were calculated for all clinical scenarios. - Disagreement dropped from 31% in the first round to 7% in the second round. Appropriateness outcomes showed specific patterns for the 3 treatments. For three-quarters of the profiles, only one treatment was considered appropriate: NSM 25%, VP 6%, and BKP 45%. NSM was usually appropriate in patients with a negative MRI or a positive MRI without other unfavorable conditions (poor outcomes for the other variables). VP was usually appropriate in patients with a positive MRI, time since fracture ≥ 6 weeks, and no spinal deformity. BKP was recommended for all patients with an ongoing fracture process, and also in most patients with a positive MRI and ≥ 1 other unfavorable factor. - The prevalence of the patient profiles in daily practice is yet unknown. - The panel results may help to support treatment choice in the heterogeneous population of patients with osteoporotic VCF.
Gesehen am 25.11.2020